From crisis to crisis: Musharraf's personal rule and the 2002 elections in Pakistan - Afaq Ansari, Zafar; Moten, Abdul Rashid (Blackwell Publishing, 2003)
It is generally acknowledged that the military is not a neutral force moving mechanically into the political arena, occasioned by a breakdown in societal equilibrium, and then returning to the barracks once the clean up or purging exercise has been completed. Rather, the military is itself a powerful political force with interests and stakes of its own, “as equally worthy of the label homo politicus as the incumbents they remove entertained.” 1 Instead of divesting themselves of political power, military governments tend, through various strategies, to stay in power. They are not nearly as preoccupied with directing the national economy for greater prosperity “as with the task of keeping themselves and their regimes afloat; they are trying to survive in a political world of great uncertainty and often turbulence.” 2 They do so by resorting to conspiracy, factional politics and clientelism, corruption, purges and rehabilitations, and various succession maneuvers. These practices are associated with a distinct type of regime called personal rule. 3 Personal rule has been remarkably persistent in the politics of developing areas.